Dialog Karya Perspektif Armada Riyanto Sebagai Jalan Kehidupan bagi Pengungsi Rohinya di Indonesia - Nara, Marianus Angi (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2024)
The Rohingya crisis is a protracted humanitarian tragedy. Thousands of Rohingya refugees have fled Myanmar and sought refuge in neighboring countries, including Indonesia. In Indonesia, they face various challenges, such as limited access to basic services, discrimination, and trauma. Dialog Karya, a concept initiated by Armada Riyanto, offers an innovative solution to address the challenges faced by Rohingya refugees. Dialog Karya combines interfaith dialog and economic empowerment through arts and culture. This approach aims to build interfaith understanding and tolerance, Empower Rohingya refugees economically through training and skills development in arts and culture. Increase public awareness to encourage support for them. Dialog Karya has the potential to have a significant positive impact on the lives of Rohingya refugees in Indonesia.